Optimization of methodology for EPS extraction and analysis - Tan, Shu Hui. (2010)
The chemical reagents ‘NaCl+HCHO’ are often used as an extractant for EPS extraction due to the neutral pH. However, there is inadequate discussion of the reagent in the literature. In this study, an extraction process using ‘NaCl+HCHO’ was examined and optimized via an investigation of the relationship between the extraction solution, centrifuge speed, ultrasound configurations and biomass concentration with the yield of extraction. Comparisons were made with extraction by ‘NaOH+HCHO’, which was found in the literature as the most effective chemical reagent for extraction to date. The Lowry and Bradford assays for protein measurement was also studied and compared. It was found that low centrifuge speed of 2000 rpm and 4000 rpm will cause biomass re-suspension. Sonication at 15 W/ml and above at 50 kHz for more than 1.5 min might lead to cell lysis. ‘NaCl+HCHO’ will only be effective at extracting biomass below 20mg. The optimized ‘NaCl+HCHO’ extraction process will use 6000rpm for centrifugation and sonication at 12.5W/ml at 50Hz for 1min. However, ‘NaOH+HCHO’ process was still more effective than the optimized ‘NaCl+HCHO’ process. Lowry assay was more effective and sensitive then Bradford assay in the range 0mg/l to 200mg/l proteins. However Lowry assay was prone to interferences and require long experimental time.